2019
DOI: 10.1177/1468017319852599
|View full text |Cite
|
Sign up to set email alerts
|

Pornography, religiosity, and social work

Abstract: Summary The effects of pornography have received increased scrutiny in the digital age. Several U.S. states have recently passed resolutions declaring pornography a public health crisis, and clients are increasingly seeking help for related concerns. Given the pornography debate encompasses micro and macro arenas, social workers have reason to be engaged. But there is a dearth of literature examining social workers' views on these issues. Given values play an integral role in informing attitudes about sexualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…If clinicians are careful to follow these new diagnostic criteria, these types of issues may be avoided. However, as previously alluded to, clinician judgment can be clouded by both personal and client individual differences (Droubay & Butters, 2019; Klein et al, 2019). Given the novelty of this diagnosis and its likely widespread integration into a variety of mental health care settings, there is a clear need to accurately understand any potential factors that may affect client self-report to more properly inform clinicians working with these clients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If clinicians are careful to follow these new diagnostic criteria, these types of issues may be avoided. However, as previously alluded to, clinician judgment can be clouded by both personal and client individual differences (Droubay & Butters, 2019; Klein et al, 2019). Given the novelty of this diagnosis and its likely widespread integration into a variety of mental health care settings, there is a clear need to accurately understand any potential factors that may affect client self-report to more properly inform clinicians working with these clients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, despite intense debates about whether CSBD represents an addictive disorder (Kowalewska et al, 2018; Kraus et al, 2016), in lay audiences, excessive pornography use is often viewed as an addiction (Perry, 2019; Taylor, 2020). There is also evidence that the application of the CSBD diagnosis can be skewed by demographic differences in clients (Klein, Briken, Schroder, & Fuss, 2019) or greater religiousness on the part of therapists (Droubay & Butters, 2019; Hecker, Trepper, Wetchler, & Fontaine, 1995). In addition, a body of prior work has suggested that self-reports of pornography addiction may be inflated for individuals for whom such sexual behaviors were in conflict with their religious or moral beliefs (Burke & Haltom, 2020; Grubbs, Perry, Wilt, & Reid, 2019; Perry, 2019), which we consider more fully below.…”
Section: Controversies Surrounding Csbd and Pornography Usementioning
confidence: 99%
“…This finding is hardly novel, as work from the late 1990s noted that sex addiction was a more commonly used diagnosis among religious therapists (Hecker et al, 1995). Similarly, much more recent work has found that religious social workers are more likely to see sexual behaviors as addictive or compulsive (Droubay & Butters, 2019). Taken with the above reviewed findings about individual religiosity and morality often contributing to feelings of addiction or compulsivity in sexual behaviors, these findings suggest that therapists need to be particularly self-aware of how personal beliefs and values might influence their conceptualizations of clients.…”
Section: Discussionmentioning
confidence: 99%
“…Others have argued that the evidence in support of such disorders is lacking (Ley et al, 2014;Prause et al, 2017). Still, others have noted that application of such diagnoses may be complicated by extraneous variables such as client or therapist religiosity or client sexual orientation (Droubay & Butters, 2019;Klein et al, 2019). Despite these controversies, the recognition of this new disorder has highlighted the need for rigorous research into out-of-control sexual behaviors and has generated new interest within clinical psychology with regards to the appropriate classification of such behaviors (for example, see: Klein et al, 2019).…”
Section: Compulsive Sexual Behavior Disorder In the Icd-11mentioning
confidence: 99%
See 1 more Smart Citation